Implementasi Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan Dalam Meningkatkan Keamanan dan Keselamatan Berlalu Lintas di Kalangan Anak Remaja di Kabupaten Pulau Morotai Tahun 2022 - Parto Sumtaki; Sri Ka’bah; Fandi Hi. Latief (Peneliti.net, 2022)
The Department of Transportation of the Morotai Island Regency which is a technical institution needs to implement policies on the system of land and inland water transportation that are interrelated with each other and fully integrated with the traffic space (roads, bridges, and or rails) which are under the regional autonomy system. This type of research is descriptive qualitative research, where the data collected is in the form of words, pictures, not numbers. Law No. 22 of 2009 concerning Road Traffic and Transportation in Improving Traffic Safety and Safety among Adolescents in its implementation is considered less than optimal, as seen from the violations committed by drivers, especially young people, which have increased significantly from year to year. This is quite reasonable, considering that Morotai Island is a group of new regencies, which is experiencing population growth, both from the exodus of people around the Morotai Island district, also followed by an increasingly rapid number of vehicle ownership. On the other hand, it is also followed by limited facilities, law enforcement officers, implementation of policies that have not hit drivers and stakeholders which have resulted in various traffic problems and traffic accidents. lack of awareness of vehicle owners (in this case parents) who provide vehicles for their children who are, on average, not old enough who do not yet have a driver's license (SIM), compared to using public transportation. This is a dilemma in making policies, on the one hand we are justified that the technical law No. 22 of 2009 regulates technical matters regarding SIM ownership, but on the other hand they think it is more effective.